Sunitinib (SU11248) in patients with chemo naive extensive small cell lung cancer or who have a 'chemosensitive' relapse: A single-arm phase II study (EORTC-08061). (February 2016) - Abdelraouf, Fatma; Smit, Egbert; Hasan, Baktiar; Menis, Jessica; Popat, Sanjay; van Meerbeeck, Jan P.; Surmont, Veerle F.; Baas, Paul; O'Brien, Mary
Abstract: Background: Targeted therapies have to date not been successful in the treatment of small cell lung cancer (SCLC). This study aimed to assess the therapeutic activity of sunitinib (an oral, multi-targeted tyrosine kinase inhibitor) using positron emission tomography (PET)–computed tomography (CT) imaging as an early indicator of response. Methods: This was a single-arm phase II study of sunitinib in patients with SCLC who are either chemo naive (extensive disease) or have a 'sensitive' relapse. A loading dose of 150 mg sunitinib was given orally followed by 37.5 mg/d. The primary end-point was disease control rate (DCR) at 8 weeks after the start of treatment and secondary end-points included toxicity of treatment and overall response. PET–CT was carried out at 4 weeks into the treatment. The study was closed early because of low accrual with only 9 of required 48 patients (19%) accrued. Results: Nine patients were registered, seven females and two males with a median age of 65 years and a median duration of sunitinib treatment of 7.4 weeks. DCR at 8 weeks was achieved in two patients, both of whom went on to long periods of disease control, one patient achieved a partial response which lasted 10 months and a second patient had stable disease (minor shrinkage) which lasted 20 months. One of these patients proved to have an atypical carcinoid tumour at rebiopsy after 10 months. DCR and PET–CT imaging both predicted these responses. Grade III–IV toxicities were encountered during treatment, most commonly neutropenia (n = 3), thrombocytopenia (n = 3) and hypermagnesaemia (n = 2). One toxic death occurred due to bronchial haemorrhage. Conclusion: This study emphasises the need for alternate study design and end-points for new drug assessment in SCLC. EudraCT number : 2006-002485-19. Highlights: 2/9 patients responded to second line sunitinib with long period of disease control. A loading dose of 150 mg of sunitinib followed by 37.5 mg per day was too toxic. Disease control at 8 weeks and PET at 4 weeks were both predictive of response.